Differential pulse anodic voltammetric determination of dapsone in pharmaceutical preparation using carbon paste and glassy carbon electrodes: application to quality control - El Ries, Mohammed A.; Salama, Nahla N.; Toubar, Safaa; El Hamid, Maha Abd; Walash, Mohammed I. (Univerzita Pardubice, 2011)
The voltammetric behavior of Dapsone has been carried out at carbon paste electrode (CPE) and glassy carbon electrode (GCE) using cyclic voltammetry and differential pulse voltammetry. Dapsone undergoes a well-defined irreversible oxidation peak at both electrodes. The proposed methods were successfully utilized for the determination of Dapsone in various dosage forms without interference from matrix with acceptable precision (RSD < 1.46 %) and accuracy (RE < 1.2 %). Forced stability studies of drug in acid, basic and oxidative media were monitored. Moreover, the CPE was used to study the in vitro release of Dapsone tablet, and testing tablet uniformity. The kinetic studies reveals first order with diffusion controlled release. The results compare favorably with data obtained by the official volumetric method.
Keywords: dapsone; cyclic voltammetry; differential pulse voltammetry; stability studies; in-vitro release